THE METHODS OF CALCULATIONS OF THE TEMPERATURE BREAKDOWN FIELD IN THE LINE OF THE MODEM HIGH-SPEED WIRE MILL - S. M. Zhuchkov; V. A. Matochkin; A. A. Gorbanev; I. V. Koshelev (Литьë и металлургия, 2007)
The calculation methods of the temperature field of the breakdown, being rolled in lines of the modern high-speed wire mill, is developed on the basis of solving of problem of the contact exchange of hot metal with cold rollers.